Extraction Of Nanocellulose And Characterization Of Migration Behaviour For Poly(Lactic Acid) Nanocellulose Silver Nanocomposite - Ivy, Gan (2019)
The objectives of this research is to study the effect of concentration of phosphoric acid (H3PO4) on the properties of cellulose nanocrystal (PCNC), examine the effect of PCNC on the properties of poly(lactic acid) PLA nanocomposites as well as the migration behaviour of silver (Ag) from PLA/PCNC/Ag nanocomposites . Three different concentrations of H3PO4 were utilized (i.e., 5M, 8M and 11M) to extract PCNC from sugarcane bagasse. The properties of the PCNC were determined by Transmission Electron Microscopy (TEM), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD) and X-ray Photoelectron Spectroscopy (XPS). TEM results showed that the aspect ratio of PCNC was reduced as the increasing concentration of the H3PO4. The aspect ratio of PCNC isolated by 5M H3PO4 was 45 and reduced to 39 when the H3PO4 was increased to 8M. The self-interaction of PCNC was induced by the P-O-P linkages (evidenced from FTIR and XPS results). XRD results showed that increased H3PO4 concentration increased the crystallinity index of the PCNC. The crystallinity index and crystal size of the PCNC was increased from 61.7 to 69.0 and 3.68 to 5.36 respectively, when the acid concentration was increased from 5M to 11M. The effect of PCNC on mechanical and thermal properties on the PLA nanocomposites was determined by using tensile test and Differential Scanning Calorimetry (DSC). The tensile modulus and strength of PLA was slightly increased by incorporation of PCNC (synthesized using 5M H3PO4). The degree of crystallinity of PLA shows highest increment which was about 51% by the addition of PCNC isolated from 5M H3PO4. The overall and specific migration test of PLA/PCNC/Ag was performed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), respectively. The migration studies show none of the PLA nanocomposites were exceeding overall migration limit (60 mg kg-1) and specific migration limit (0.05 mg kg-1). Nonetheless, it was found that the PCNC can acts as carrier for Ag from the PLA nanocomposites and this influencing the migration behaviour of the Ag nanoparticle.